Wheelset-rail mechanical model for a steady-state dynamic condition and prediction of rolling contact fatigue locci. Issue 1 (2nd January 2022) - Higa, Debora Naomi; Kina, Edilson Jun; Gay Neto, Alfredo
Abstract : In railway heavy haul transportation, the wheel-rail contact interaction has a strong influence on the performance of the entire system. According to the vehicle longitudinal movement conditions - straight/curved tracks and travel speed, contact interaction takes place on different portions along the wheel/rail geometric profiles. Determining wheel/rail contact patches is fundamental both for vehicle dynamics and to predict the locci prone to rolling contact fatigue (RCF), due to high contact pressures. This work presents a quasi-static model to determine the wheel-rail contact locations and pressures for a given steady-state scenario of straight or curved track. The model is able to consider generic wheel and rail profile geometries with several contact pointwise interactions. Each contact pair is solved by the called 'master-master methodology', developed generally for a 3D environment. A proposed simplification leads to a two-dimensional model, able to produce results in fast processing time and very low computational cost. The result gives predictions related to RCF-prone location. The model is motivated for application together with a methodology to quantify the accumulated contact pressure, considering a family of distinct wheelsets and their combined interactions with the rails. We present a case study considering real measured wheel and rail profiles.